Inulin-type dietary fiber stability after combined thermal, mechanical, and chemical stresses related to ultrasound processing of prebiotic apple beverage. (May 2023) - Strieder, Monique M.; Arruda, Henrique S.; Pastore, Glaucia M.; Silva, Eric Keven
Abstract: Inulin-type fructans are promising prebiotic dietary fibers added to foods and beverages to aggregate functional properties. In this regard, this study examined the chemical and physical stability of inulin after thermal, mechanical, and chemical stress conditions provided by high-intensity ultrasound treatment. The objective was to investigate the behavior of the inulin molecular structure and its technological issues under high-energy processing to understand the feasibility of adding inulin to new products with health benefits. Temperature monitoring during high-intensity ultrasound processing was crucial because high temperatures of up to 82 ± 1 °C were reached using short processing times of up to 5.48 min. Despite the temperature rise, ultrasound specific energies of 30, 120, 210, and 300 J/g did not affect the pH, soluble solid content, total phenolic content, antioxidant activity, and sugar content of the inulin-enriched apple beverage. In addition, the ultrasound processing stresses promoted by acoustic cavitation did not modify the profile and content of the short chain inulin added to the apple juice. The specific energy of 300 J/g contributed to the physical stability of the prebiotic apple beverage because this high-energy condition inhibited inulin precipitation producing a less cloudy product. Inulin was stable to high-energy ultrasound treatment because its molecular integrity was preserved. Moreover, the nutritional and bioactive compounds of the apple beverage were stable against acoustic cavitation-induced degradation. On the other hand, inulin precipitated in the aqueous solution after cooling of samples treated up to 210 J/g clouding the apple beverage. Indeed, high-intensity ultrasound processing enhanced the technological attributes of the prebiotic beverage, preventing its clouding due to inulin precipitation. Sonication treatment increased the physical stability of the beverage because it increased the magnitude of zeta potential. Graphical abstract: Image 1 Highlights: Inulin precipitated making cloudy the prebiotic apple beverage after cold storage at 7 °C. Higher ultrasound specific energy inhibited the inulin precipitation in the clarified apple juice. Ultrasound increased the zeta potential of apple beverages enhancing their physical stability. Ultrasound processing up to 300 J/g did not modify the profile and content of fructooligosaccharides. Phenolic compounds, antioxidant activity, and sugar content were preserved up to 300 J/g.